The single scattering albedo Angstrom exponent of black carbon with brown coatings. (January 2021) - Zhang, Xiaolin; Mao, Mao; Chen, Hongbin; Tang, Shihao
Highlights: BC with non-absorbing coating for large size or thick coating may show negative SSAAE. The SSAAE of BC with brown coating are studied with recent observations. Sensitivities of SSAAE of coated BC to its microphysics are numerically studied. BC with brown coating may exhibit positive SSAAE for thin coating or small-sized coated BC. Separating brown carbon from black carbon with a criterion of negative SSAAE shows limitation. Abstract: The single scattering albedo is a significant parameter obtaining the magnitude and sign of radiative forcing of aerosols, whereas our understanding of single scattering albedo Angstrom exponent (SSAAE) is still limited, especially for black carbon (BC) particles with brown coating. This study employs the accurate multiple-sphere T-matrix method to numerically evaluate the influences of aerosol microphysics on the SSAAE of coated BC aggregates. The SSAAE of coated BC shows strong dependences on absorbing volume fraction of coating, shell/core ratio, and size distribution, whilst it generally exhibits weak sensitivities to BC fractal dimension, BC position inside coating, and coated volume fraction of BC. Higher SSAAE values are seen for coated BC with less absorbing volume fraction of coating, lower shell/core ratio, or smaller particle size. BC particles coated by brown carbon for various size distributions have a wide variation of SSAAE between 350 nm and 550 nm with a range of -0.95–0.48, while the SSAAE at larger wavelengths (between 550 nm and 700 nm) shows higher values. Our study reveals that BC with non-absorbing coating can show negative SSAAE for thick coating or large size, and BC with brown coating may exhibit positive SSAAE for thin coating or small-sized coated BC, indicating the limitation of separating brown carbon from black carbon with a criterion of negative SSAAE.